Leadership Of Tanjung Pisang Village Head Of Kuantan Hilir Seberang Kuantan Singingi Regency In Implementing Village Development - Data Wardana; Rocky Multapea (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2021)
Village administration has a very important role in the implementation of development. One of the functions of government is the function of development. The importance of leadership style applied to subordinates in accordance with the maturity/maturity of subordinates is an absolute requirement for leadership effectiveness in organizational success. This research is about the village head's leadership in development in Tanjung Pisang Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency in implementing village development. The problem that occurs is that the implementation of development does not involve community participation. In this study using qualitative research methods in order to find solutions to all problems. The results of the study show that there is no good cooperation between the village head and the community. so that community participation does not materialize. In addition, the delegation of tasks is not accompanied by the provision of understanding to subordinates so that the work is not completed according to the allotted time.